The Use of the Aussprachetraining Web-Based Application on German Pronunciation - Talitha Rabbani (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2026)
This research examines the use of the Aussprachetraining web-based application developed by the Goethe-Institut in improving students’ German pronunciation skills as well as explores their perceptions of this technology. Utilizing a mixed-methods sequential explanatory design, the study analyzed data from 39 first-year students of the German Studies Program through pre- and post-tests, activity logs, and questionnaires. The quantitative analysis demonstrated a 3.28% improvement in average pronunciation scores, which increased from 78.45 to 81.03, alongside high engagement levels where over 66% of participants achieved significant accuracy within the application-based exercises. Qualitatively, the students reported a positive experience, specifically highlighting the visually appealing interface (66.67%), its user-friendly navigation (71.79%), and the relevance of its content to course materials (69.23%). The most helpful feature identified was the immense value of native speaker pronunciation models. Despite these benefits, the study identified critical technical limitations, particularly regarding the accuracy of the speech recognition system and the quality of automated feedback, which the majority of respondents found suboptimal. This research concludes that, while the application proves to be a powerful tool for fostering self-directed learning and increasing learner confidence, technical refinements are necessary to maximize its effectiveness.